2001
DOI: 10.1045/july2001-vandesompel
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing the OpenURL Framework beyond References to Scholarly Works

Abstract: This paper describes the attempts of the COHSE project to define and deploy a Conceptual Open Hypermedia Service. Consisting of and integrated to form a conceptual hypermedia system to enable documents to be linked via metadata describing their contents and hence to improve the consistency and breadth of linking of WWW documents at retrieval time (as readers browse the documents) and authoring time (as authors create the documents).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…A search of the Internet did not substantially add to the body of literature described above. It was, however, a useful reservoir of information about OpenURL link resolvers with small market share and it provided reinforcement in other cases by presenting more technology descriptions [33,32] more product descriptions and screen captures [6,10,11,13,14,17,22,23,26,27,29,30] and library-specific experiential information. Based on this literature review, it was concluded that there were no published critical comparisons of commercially available link resolver products in either the published professional literature or on the open Web.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A search of the Internet did not substantially add to the body of literature described above. It was, however, a useful reservoir of information about OpenURL link resolvers with small market share and it provided reinforcement in other cases by presenting more technology descriptions [33,32] more product descriptions and screen captures [6,10,11,13,14,17,22,23,26,27,29,30] and library-specific experiential information. Based on this literature review, it was concluded that there were no published critical comparisons of commercially available link resolver products in either the published professional literature or on the open Web.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some work has begun on the development of standards in this area, to facilitate the identification and obtention of specific articles taking into account standard information obtained from the citation. Among these are the Open‐URL (Van de Sompel & Beit‐Arie, 2001) and DOI (Rosenblatt, 1997) initiatives, that have been used in the development of SFX and Cross‐Ref projects respectively, but much work remains to be done on the acceptance and implementation of standards before they can be effectively functional. Programming obstacles due to the refusal of some of the service providers to incorporate standard protocols into their search systems continue to dog the development of integrated information solutions.…”
Section: Chaos To Cosmosmentioning
confidence: 99%
“…A possible approach to 'deep citation' (the referencing of subsets of an information object identified by a DOI) is the use of OpenURL ( Van de Sompel & Beit-Arie, 2001) to convey a query payload to the resource identified by the DOI. An implementation of this approach by CrossRef allows deep citing of content within International Tables for Crystallography Online (http://it.iucr.org) and may be a useful model for further investigation in the context of data sets.…”
Section: Discoverability Through Persistent Identifiersmentioning
confidence: 99%